Bioaccumulation of Trace Metals in Mussel (Mytilus galloprovincialis) from Mali Ston Bay during DSP Toxicity Episodes - Ivana Ujević; Nenad Vuletić; Jelena Lušić; Nikša Nazlić; Grozdan Kušpilić (Molecules, 2015)
The Croatian National Monitoring Program revealed the presence of Diarrhetic Shellfish Poisoning (DSP) toxicity in Mediterranean blue mussel (Mytilus galloprovincialis) from breeding farms in southern Adriatic Sea through January to June 2011. The mouse bioassay tests (MBA; at the time the official method for DSP toxins) were accompanied by atypical symptomatology in the animals and this caused doubts about the assay results. Consequently, in parallel studies reported here, the concentration of Cd, Cr, Cu, Ni, Pb and Zn in soft tissue of DSP positive and negative mussels samples was determined. Cd, Cr, Zn and Ni show higher values in approximately 75% of the DSP positive samples, whereas for Pb and Cr the values were 26% and 34%, respectively. This trend was unchanged during the whole observation period.